Analysis of Titanium Mesh Ti6Al4V Formation Using Die Press Forming Machine for Cranioplasty - Rizal, Ahmad Ayyub Syaiful; Darsin, Mahros; Wibowo, Robertoes Koekoeh K.; Anam, Khairul (Universitas Negeri Malang, 2024)
Cranioplasty is required for patients with head defects, where the deformed part of the head is replaced with Ti6Al4V titanium wire implants. The titanium wire forming process is usually done manually, which can take a long time and give results that do not match the anatomical shape of the head. Therefore, it is important to develop domestic technology that can produce titanium wire automatically. This study aims to analyze the frame and mold of the automatic wire mesh molding machine before production. The tool is made using press forming method and finite element analysis with ANSYS software. The machine frame is made of 304 stainless steel material, while the mold uses ABS material. The analysis was performed with a constant load force of 100 N, corresponding to the maximum reading on the load cell. The simulation results show the deformation, strain, and von Mises stress of the machine frame and punch model, which are still far below the plastic deformation and UTS values of the material. However, the analysis results on the Ti6Al4V titanium die and mesh exceeded the UTS of the material in the cutting edge area of the die. Nevertheless, the die model can still be used because the maximum stress point is located at the edge of the die design area, where the titanium mesh will be cut when applied to the patient's skull implant. The results of this study are expected to help medical personnel in skull implant surgery and analysis of press machine manufacturing.